Upaya Guru Paud Dalam Menanamkan Karakter Kebangsaan Melalui Pendidikan Kewarganegaraan Bagi Anak Usia Dini - Patola, Sinta; Marampa, Elieser R; Sitorus, Johnson; Sinlae, Demsi Yanto (University of Muhammadiyah Malang, 2023)
The aim of this research is to analyze and determine the efforts of PAUD teachers in forming children's national character from an early age through citizenship education. In this research, researchers used library research by collecting and analyzing various sources such as journal articles, PDF drives and books related to the problems that will be solved through this research. In the process of collecting data from various related sources, the researcher did it carefully in order to ensure that the information or data obtained was truly accurate so that the results of this research show that: (1) Early childhood education is a valuable opportunity to develop an attitude of love. peaceful, responsible and with national character such as love of the homeland, respect for the values ​​of Pancasila and diversity; (2) PAUD teachers have a very strategic role in forming national character in early childhood through instilling civic values ​​in order to prevent children from committing criminal acts in the future. Data analysis was carried out using a qualitative approach, with a focus on identifying patterns, main findings or previous research, and relationships between concepts that emerged from the sources collected. Researchers evaluated information to form an in-depth understanding of PAUD Teachers' efforts to instill or shape national character through Citizenship Education for early childhood.